2020
DOI: 10.1159/000512167
|View full text |Cite
|
Sign up to set email alerts
|

Mucosa-Associated Microbiota in Patients with Irritable Bowel Syndrome: A Comparison of Subtypes

Abstract: <b><i>Background:</i></b> Most studies on gut microbiome of irritable bowel syndrome (IBS) have focused on fecal microbiota, instead of mucosa-associated microbiota (MAM). <b><i>Aims:</i></b> The aim of this study wasto investigate the MAM in IBS patients including the difference in subtypes of IBS, namely, diarrhea-predominant IBS (IBS-D) and constipation-predominant IBS (IBS-C). <b><i>Methods:</i></b> Endoscopic brush samples were taken … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 27 publications
1
14
0
Order By: Relevance
“…Animal models and case studies of patients have shown that members of the Erysipelotrichaceae family are significantly increased in a number of inflammatory conditions [ 47 ], such as irritable bowel syndrome [ 48 ], colorectal cancer [ 47 ], and rheumatoid arthritis with anti-citrullinated protein autoantibodies [ 49 ], suggesting a pro-inflammatory effect of this bacterial family on the host. Previous studies report an association between abundance of Erysipelotrichaceae family members and host lipidemic profile, particularly relating to cholesterol levels [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Animal models and case studies of patients have shown that members of the Erysipelotrichaceae family are significantly increased in a number of inflammatory conditions [ 47 ], such as irritable bowel syndrome [ 48 ], colorectal cancer [ 47 ], and rheumatoid arthritis with anti-citrullinated protein autoantibodies [ 49 ], suggesting a pro-inflammatory effect of this bacterial family on the host. Previous studies report an association between abundance of Erysipelotrichaceae family members and host lipidemic profile, particularly relating to cholesterol levels [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mucosal samples were obtained under BAE by gently brushing the mucosal surfaces with a COOK medical endoscopy cytology brush (Cook Medical, Tokyo, Japan) [5]. BAE was performed by experienced endoscopists using the Fujinon double-balloon endoscopy system (Fuji Photo Optical, Saitama, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…The human gastrointestinal (GI) tract contains approximately 10–100 trillion bacteria from 500 to 1,000 distinct species collectively known as gut microbiota [1]. The composition of the gut microbiota affects human health and is involved in the pathology of various diseases, not only GI diseases such as GI malignant tumor [2], inflammatory bowel disease [3], and functional GI disorders [4, 5] but also ranging from metabolic disease and inflammatory diseases to behavioral and physiological abnormalities such as autism spectrum disorder [6]. These organisms can alter the metabolic profile of the host, including its carbohydrate, amino acid, and lipid metabolism [7].…”
Section: Introductionmentioning
confidence: 99%
“… 9 MAM reflects mucosal barrier function more directly than fecal microbiota and is reportedly involved in the pathogenesis of many diseases, such as intestinal diseases like inflammatory bowel disease and extraintestinal diseases including liver disease. 21 , 22 , 23 , 24 , 25 The overgrowth of MAM is associated with the pathogenesis of primary biliary cirrhosis. 26 This study analyzed the characteristics of MAM in early‐stage NAFLD and the differences between fecal microbiota and MAM.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the gut microbiota consists of the luminal microbiota (including fecal microbiota) and MAM (present in the intestinal mucosa) 9 . MAM reflects mucosal barrier function more directly than fecal microbiota and is reportedly involved in the pathogenesis of many diseases, such as intestinal diseases like inflammatory bowel disease and extraintestinal diseases including liver disease 21‐25 . The overgrowth of MAM is associated with the pathogenesis of primary biliary cirrhosis 26 .…”
Section: Discussionmentioning
confidence: 99%